Targeted Isolation of Antioxidant Constituents from Plantago asiatica L. and In Vitro Activity Assay - Yuanyang Dong; Qihang Hou; Meng Sun; Jingjing Sun; Bingkun Zhang (Molecules, 2020)
Plantago asiatica L. is widely distributed in Eastern Asia and a commonly used drug in China, Korea, and Japan for diuretic and antiphlogistic purposes. In this experiment, the present study was performed to isolate antioxidant molecules based on the DPPH scavenging activity assay and discover the bioactive compounds which contributed to performing the function of Plantago asiatica L. Each faction was chosen for further isolation guided by DPPH scavenging activity assay. Afterwards, two potential bioactive molecules, aesculetin and apigenin, were isolated for in vitro antioxidant activity in cells. Hydrogen-peroxide-induced oxidative stress led to decreased cell viability, impaired intercellular junction, and damage to the cell membrane and DNA. Furthermore, aesculetin ameliorated decreased cell viability induced by hydrogen peroxide via upregulation of antioxidant related genes, and apigenin also protected against H2O2 mainly by improving the glutathione (GSH) antioxidant system, such as increasing the activity of glutathione peroxidase (GPX), glutathione reductase (GR), and the ration of GSH/glutathione disulfide (GSSG). Above all, these findings suggest that aesculetin and apigenin may be bioactive compounds for antioxidant function in Plantago asiatica L.